1997
DOI: 10.1016/s0899-3289(97)90011-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating DSM-IV alcohol dependence and abuse by course: Community heavy drinkers

Abstract: The purpose of this study was to investigate the differences in shortterm course between DSM-IV alcohol abuse and alcohol dependence in a community

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 12 publications
7
88
0
2
Order By: Relevance
“…Although both factor and latent class models have been previously used to explain the population aggregation of AD symptoms (Allen et al, 1993), no clear structure has emerged. A FA approach seeks to understand the underlying continuous dimensions for symptoms, which is an important initial stage of developing constructs in the use or abuse either of a single substance (Harford and Muthen, 2001;Hasin et al, 1997;Lennox et al, 1996) or of a variety of substance disorders (Nelson et al, 1999) but is more difficult to provide direct clinical applications, such as treatment response and evaluation. While LCA models frequently support a severity-based classification in alcohol problems (Bucholz et al, 1996;Lynskey et al, 2005) or cannabis use , the symptom profiles from these analyses appear largely parallel, and involve relatively small differences in item endorsement probability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both factor and latent class models have been previously used to explain the population aggregation of AD symptoms (Allen et al, 1993), no clear structure has emerged. A FA approach seeks to understand the underlying continuous dimensions for symptoms, which is an important initial stage of developing constructs in the use or abuse either of a single substance (Harford and Muthen, 2001;Hasin et al, 1997;Lennox et al, 1996) or of a variety of substance disorders (Nelson et al, 1999) but is more difficult to provide direct clinical applications, such as treatment response and evaluation. While LCA models frequently support a severity-based classification in alcohol problems (Bucholz et al, 1996;Lynskey et al, 2005) or cannabis use , the symptom profiles from these analyses appear largely parallel, and involve relatively small differences in item endorsement probability.…”
Section: Discussionmentioning
confidence: 99%
“…While it is still in debate whether abuse should be included in the same continuum as dependence, AD appears to be a more reliable unitary construct. In addition, two prospective studies used general population samples have indicated that the course of AD differs from that of abuse (Hasin et al, 1990;Hasin et al, 1997), and implied that alcohol dependence and abuse are different in nature. Because alcohol abuse and dependence also have different features in terms of their clinical presentation, etiology and demographic characteristics (Hasin et al, 2007), we focus on only alcohol dependence for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of the AUDADIS-IV alcohol diagnoses is documented in clinical and general population samples Grant et al, 2003a;Hasin et al, 1997a) with test retest reliability ranging from good to excellent (κ = 0.70-0.84). Convergent, discriminant, and construct validity of AUDADIS-IV alcohol use disorder criteria and diagnoses were good to excellent (Hasin and Paykin, 1999;Hasin et al, 1990Hasin et al, , 1994Hasin et al, , 2003Hasin et al, , 1997c, including in the World Health Organization/National Institutes of Health International Study on Reliability and Validity Hasin et al, 1997b;Nelson et al, 1999;Pull et al, 1997;Ustun et al, 1997;Vrasti et al, 1998), where clinical reappraisals documented good validity of DSM-IV alcohol use disorder diagnoses (κ = 0.60-0.76) (Canino et al, 1999;Cottler et al, 1997;Hasin et al, 1997b;Nelson et al, 1999;Pull et al, 1997;Ustun et al, 1997;Vrasti et al, 1998).…”
Section: Source Of Datamentioning
confidence: 99%
“…DSM-IV nomenclature suggests that abuse should occur before dependence (pertaining to the same drug) and that only a subset of persons who experience abuse should advance to experience dependence (APA, 1994). Both of these expectations regarding the association between abuse and dependence diagnoses have been refuted empirically (Hasin & Grant, 2004;Hasin, Van Rossem, McCloud, & Endicott, 1997;Ridenour et al, 2003;Schuckit et al, 2001). Ridenour et al (2003) argued that the environmental element of each abuse criterion makes them impure measures of individuals' drug misuse.…”
Section: Obstacles Of Human Addiction Diagnostic Phenotypesmentioning
confidence: 99%